Europe's infrastructure transition : economy, war, nature - Högselius, Per; Kaijser, Arne; Vleuten, Erik van der (Making Europe : Technology and Transformations, 1850-2000, 2016)
Europe's Infrastructure Transition captures the conflicted story of European integration. We learn of the priorities set, the choices made in constructing infrastructure connections-within and beyond the continent. And we see how Europe's infrastructure both united and divided people and places via economic systems, crises, and wars.
Keywords: Infrastructure (Economics) : Europe : History; taloushistoria; infrastruktuurit; integraatio; yhteiskuntakehitys; luonto; sodat; vaikutukset; ekonomisk historia; infrastruktur; integration; samhällsutveckling; naturen; krig; effekter; Europe : Economic integration : History; Europe : History; Eurooppa; Europa